1995
DOI: 10.1074/jbc.270.46.27601
|View full text |Cite
|
Sign up to set email alerts
|

A Single Mutation of the Neurokinin-2 (NK2) Receptor Prevents Agonist-induced Desensitization

Abstract: Receptor activation and agonist-induced desensitization of the human neurokinin-2 (NK2) receptor expressed in Xenopus oocytes have been investigated. When neurokinin A (NKA) was applied repeatedly at 5-min intervals, the second and subsequent applications gave no responses. This desensitization was not observed with the specific agonists (Lys3, Gly8-R-gamma-lactam-Leu9)NKA(3-10) (GR64349) or (Nle10)-NKA(4-10). However, in the presence of the protein kinase inhibitor staurosporine, stimulation with GR64349 or (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…We showed that two natural agonists, NKA and its truncated form, NKA-(4 -10) (24), differed in that NKA triggers rapidly desensitizing calcium responses, whereas repetitive NKA-(4 -10) administration did not alter cell responsiveness (23,25), supporting the conclusion that at least part of response desen-sitization to NKA was due to lack of receptor responsiveness.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…We showed that two natural agonists, NKA and its truncated form, NKA-(4 -10) (24), differed in that NKA triggers rapidly desensitizing calcium responses, whereas repetitive NKA-(4 -10) administration did not alter cell responsiveness (23,25), supporting the conclusion that at least part of response desen-sitization to NKA was due to lack of receptor responsiveness.…”
supporting
confidence: 58%
“…It differs from NKA in that it repetitively activates intracellular calcium release both in oocytes (25) and HEK 293 cells (23) expressing the NK2R, and may be viewed as a "non-desensitizing" agonist with respect to calcium signaling. The fluorescent version of NKA-(4 -10) labeled with Texas Red used here, TR7-NKA-(4 -10), exhibits an apparent single step association to EGFP-NK2R that temporally correlates with the development of an intracellular calcium response (in the second to minute time range).…”
Section: Discussionmentioning
confidence: 99%
“…The NK2 termination codon was TGA. Functional wild type NK2 expressed in Xenopus oocytes was characterized by inward currents of 1-4 A that appeared within 2-4 s after application of the natural agonist NKA and slowly decayed over 10 -20 s, corresponding to the activation of calcium-dependent chloride channel (24,30) (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Saturation binding assays with PhCO-(␦-125 I-phenol-3-propionyl)-Orn-Ala-D-TrpPhe-D-Pro-Pro-Nle-NH 2 (0.1-10 nM) were performed as described previously (24). Nonspecific binding was determined in the presence of…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation